The Cultural Dynamics of Power and Corruption in Local Government Department, District Swabi, Khyber Pakhtunkhwa, Pakistan - Muhammad Tufail; Muhammad Taieb (Journal of Management Practices, Humanities and Social Sciences, 2023)
The purpose of the study is to explore the cultural dynamics and patterns of misuse of authority in the local government department at the district Swabi, in Khyber Pakhtunkhwa province of Pakistan. The main focus of the study is to identify that who are the real stakeholders holding the power in the local government department, how corruption is done by these powerful stakeholders, what are the patterns of power execution and what are the implications of the misuse of authority for the local communities. The study is based on the social exchange theory of anthropology. The study is qualitative in nature. Purposive and snowball sampling methods are used. The minimum sample size is 270 and the maximum sample size is indefinite and depends on the saturation of the same frequent information. Data is collected via unstructured interviews and case studies. The major finding of the study is that there exists an informal network of liaison among the three actors, holding and sharing the power and authority as partners, in the local government. The three actors working as partners in this liaison were identified as: the local government officials, the local community leaders, and the government contractors. This informal network of liaisons is holding and sharing the power and authority to obtain, maintain and secure social, political, and monetary benefits. This liaison has established an informal system of power and authority that is exercised through its own informal structure. This informal system is working parallel to the formal legal system of the government. The Laws, regulations, rules, and procedures set for the public administration and governance are used to be technically evaded and dodged by these partners to secure their vested interests. The vested interests were identified as: keeping control over the power and authority sources, misuse of authority to collect the wealth, and to buy the means of pleasures and luxuries. This informal power liaison seeks and secure support from the provincial and federal government authorities. This support is obtained via the payments of cash money, luxurious gifts, and services. This informal system of liaison always controls and obtains the awards of the contracts of the development and non-development works and services in the local government. They save illegal money in these contracts through various methods identified with the names as: the acceptances, the advances, the commissions, and the local taxations. The local communities are controlled and kept satisfied via the local touts. The loyalty of these touts is bought via the provision of government jobs, contracts of developmental works and services and payments of cash money. The local cultural patterns of interdependence and social exchanges based on kinship ties, neighborhoods, friendship, and political affiliations provide the ground for corruption.